Technology forecast by analogy and environmental analysis for technology X - a decision support tool for disaster response preparedness - Lee, Agnes Meiling C. (University of the Philippines Diliman, 2016)
This study presents a forecast and environmental analysis for Technology X - a decision support tool for disaster response preparedness in the Philippines. The project is being developed by a premier university in the country, through funding from the Department of Science and Technology. While the project team is dedicated to the full development of technical features of the tool, there is little focus given to the formulation of strategies on how the tool will be adopted by its target users. Failure to conduct successful technology transfer and seamless adoption would compromise the achievement of the full impact of this relevant government-funded technology.